Niger: Impacts of COVID-19 on Production, Poverty and Food Systems - Pauw, Karl; Randriamamonjy, Josee; Sangare, Saadatou A.; Thurlow, James (2020)
By Karl Pauw, Josée Randriamamonjy, Alkassoum Sangaré Saadatou, and James Thurl